Research project and thesis. Guide for its preparation - Oscar Bonet Collazo; Antonio Mazot Rangel; María Casanova González; Nicolás Ramón Cruz Pérez (Medisur)
The final research that residents must carry out to complete the specialization is the instrument created in the postgraduate training process, so that they learn and apply the basic aspects of medical research methodology. This work aims to provide a reference guide for students and teachers, on the structure and presentation of research projects and final report of completion of the specialty. For this, a bibliographic search was carried out for the compilation and classification of the updated bibliography. Considerations of how to prepare the research project and the final report are provided, and the information that both documents must have is specified. Fundamental elements on the structure and presentation of research projects and final report that can be used as a reference guide for students and teachers are exposed.